Performance of DNA methylation‐based biomarkers in the cervical cancer screening program of northern Portugal: A feasibility study. Issue 11 (12th September 2021) - Salta, Sofia; Maia‐Moço, Leonardo; Estevão‐Pereira, Helena; Sequeira, José Pedro; Vieira, Renata; Bartosch, Carla; Petronilho, Sara; Monteiro, Paula; Sousa, Ana; Baldaque, Inês; Rodrigues, Jéssica; Sousa, Hugo; et al.
Abstract: Cervical cancer remains a health concern. Effective screening programs are critical to reduce the incidence and mortality. High‐risk HPV (hr‐HPV) testing as primary screening tool discloses high sensitivity but suboptimal specificity. Adequate triage tests to reduce unnecessary colposcopy referrals and overdiagnosis/overtreatment are crucial. Hence, we aimed to validate a panel of DNA methylation‐based markers as triage test for women hr‐HPV+ in the population‐based Regional Cervical Cancer Screening Program of Northern Portugal. Firstly, CADM1, MAL, FAM19A4 and hsa‐miR124‐2 promoter methylation levels were assessed by multiplex QMSP in a testing set of 402 FFPE tissue samples (159 normal samples and 243 cervical lesions, including 39 low‐grade intraepithelial squamous lesions [LSIL], 59 high‐grade intraepithelial squamous lesions [HSIL] and 145 cancerous lesions). Then, preliminary validation was performed in 125 hr‐HPV+ cervical scrapes (including 59 normal samples, 30 LSIL, 34 HSIL and 2 cancerous lesions). Higher MAL me, FAM19A4 me and hsa‐miR124‐2 me methylation levels were disclosed in histological HSIL or worse (HSIL+) in testing set. Individually, markers depicted over 86% specificity for HSIL+ detection. In validation set, all these genes significantly differed between histological HSIL+ and low‐grade squamous intraepithelial lesions or less. In combination, these markers reached 74% specificity and 61% sensitivity for identification of histological HSIL+. We concluded that host gene methylation might constitute a useful referral triage tool of hr‐HPV+ women enrolled in the Cervical Cancer Screening Program of Northern Portugal. Abstract : What's new? For cervical cancer screening, high‐risk HPV (hr‐HPV) testing is highly sensitive, but for those who test positive, a more specific test is needed to reduce unnecessary colposcopy. Here, the authors validated a panel of DNA methylation‐based markers to screen hr‐HPV+ women. They measured promoter methylation of four genes, CADM1, MAL, FAM19A4, and hsa‐miR124‐2, in cervical samples including normal tissue, low‐ and high‐grade squamous intraepithelial lesions (LSIL and HSIL) and cancerous lesions. The markers showed 74% specificity for HSIL or cancer, indicating that DNA methylation could be a useful triage tool for hr‐HPV+ women.